Clinical Features and Risk Factors of Pulmonary Hypertension in Chinese Patients With Systemic Lupus Erythematosus - Xiangfang CHEN; Wenzhong QUE; Xiangxiong ZHENG; Shiwen ZOU; Pin LI; Xuwei YANG (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the systemic lupus erythematosus (SLE) frequency, clinical characteristics, and laboratory features of pulmonary hypertension (PH) in a Chinese population with SLE and to evaluate the risk factors contributing in early diagnosis. Patients and methods: A total of 39 patients (2 males, 37 females; mean age 38.2±14.9 years; range, 16 to 71 years) with combined SLE and PH and 407 patients (43 males, 364 females; mean age 34.8±14.0 years; range, 7 to 73 years) with SLE but without PH (NonPH) were enrolled and categorized into two groups, namely, PH and NonPH groups. The demographic and clinical characteristics of all patients, including disease duration, comorbidity, malar rash, epilepsy, arthritis, oral ulcer, photosensitivity, Raynaud’s phenomenon, serositis, dyspnea, and visceral damage, were recorded. Laboratory parameters, including blood and urine routine, biochemical markers, 24-hour proteinuria, plasma N-terminal pro-brain natriuretic peptide (NT-proBNP), immunoglobulin, complement 3 and 4, and autoantibodies, were tested. Inflammatory indexes, such as erythrocyte sedimentation rate and C-reactive protein level, were collected. Disease activity was assessed with systemic lupus erythematosus disease activity index score. Organ damage was assessed with the use of Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (SLICC/ACR-DI; SDI). Pulmonary arterial systolic pressure was measured using echocardiography. Results: Pulmonary hypertension frequency in our Chinese population with SLE was 8.74%. Statistical differences in neuropsychological symptoms, epilepsy, serositis, Raynaud’s phenomenon, tachypnea, albumin, creatinine, abnormal electrocardiograph, urine protein, urine red blood cell rate, NT-proBNP, Body Mass Index, SDI and duration of SLE were found between SLE patients with or without PH. Multivariate logistic regression revealed that Raynaud’s phenomenon, serositis, tachypnea, epilepsy, and positive anti-U1 small nuclear ribonucleoprotein (U1RNP) were significant risk factors for PH in SLE. Conclusion: Chinese patients with SLE are at high risk for PH if they present with epilepsy, Raynaud’s phenomenon, serositis, tachypnea, and positive anti-U1RNP. Echocardiography is highly recommended to be performed on Chinese patients with SLE for the screening of PH.